THE ASSOCIATION OF SQUAMOUS KERATINIZING METAPLASIA (LEUKOPLAKIA) OF THE BLADDER WITH SYMPTOMS OF THE LOWER URINARY TRACT IN WOMEN - Markovski, Darko (Българско урологично дружество, 2024)
INTRODUCTION: Squamous keratinizing metaplasia (SCM) of the bladder, also known as leukoplakia of the bladder, is a condition in which the normal transitional epithelium is transformed into a squamous epithelium overlying a layer of keratin (1). In most patients, typical non-specific urinary symptoms are expressed, such as frequency, urgency, suprapubic pain, discomfort, microhematuria and, less often, macrohematuria (7). OBJECTIVES OF THE STUDY: - To prove the relationship between bladder leukoplakia and urinary symptoms in affected women. - To determine the effect of endoscopic resection of leukoplakia in relation to conservative treatment MATERIALS AND METHODS: The study analysed 50 patients with long term lower urinary tract symptoms (more than six months) between 2021 and July 2024. All underwent cystoscopy. The study included patients with a pathohistological diagnosis of squamous keratinizing metaplasia of the bladder. The severity of symptoms was determined according to the international classification for urinary symptoms (International prostate symptom score - IPSS). Bi-polar transurethral resection of squamous keratinizing metaplasia of the bladder was performed in all patients. One month after the intervention, the patients were called for a follow-up examination, during which the severity of urinary symptoms was re-evaluated according to the IPSS. Then a comparative analysis was performed, on the basis of which the significant difference of IPSS before and after the intervention was assessed. RESULTS: Of the total number of female patients, lower urinary tract symptoms, pain and hematuria were the most common symptoms. After the intervention there was a significant improvement in the initial IPSS score. The percentage of patients with severe and moderate lower urinary tract symptoms decreased from 57.1% to 25.7%. No hematuria was reported, and most of the patients reported an improvement in their quality of life. A total of 64.4% of patients reported an improvement in symptoms, in 23.5% there was no improvement, and 12.1% reported worsening of symptoms. CONCLUSION: Bipolar transurethral resection significantly relieves symptoms in women with squamous keratinizing metaplasia, improves quality of life according to the IPSS questionnaire by an acceptable 64.4%, and is superior to conservative treatment